2013
DOI: 10.1371/journal.pone.0083081
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for Triple-Negative Breast Cancer Patients Based on Node Status, Cathepsin-D and Ki-67 Index

Abstract: ObjectiveThe aim of this study was to evaluate clinicopathologic factors that could possibly affect the outcome of patients with triple negative breast cancer and subsequently build a prognostic model to predict patients’ outcome.MethodsWe retrospectively analyzed clinicopathologic characteristics and outcome of 504 patients diagnosed with triple-negative invasive ductal breast cancer. 185 patients enrolled between 2000 and 2002 were designated to the training set. The variables that had statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
(30 reference statements)
3
24
0
1
Order By: Relevance
“…Nevertheless, many researchers have observed that tumor size or LN status have a significant association with DFS or OS in TNBC patients [14162021]. Thus, the MNPI, which is calculated with input from tumor size, LN stage, and modified histologic grade, appears to be theoretically appropriate to predict the prognosis of patients with TNBC, and our study revealed that the MNPI is the most significant prognosticator for DFS, DMFS, and OS.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Nevertheless, many researchers have observed that tumor size or LN status have a significant association with DFS or OS in TNBC patients [14162021]. Thus, the MNPI, which is calculated with input from tumor size, LN stage, and modified histologic grade, appears to be theoretically appropriate to predict the prognosis of patients with TNBC, and our study revealed that the MNPI is the most significant prognosticator for DFS, DMFS, and OS.…”
Section: Discussionmentioning
confidence: 53%
“…However, in most studies of TNBC patients, the prognostic significance of nodal status was evaluated by the number of positive LNs, not NR. These studies demonstrated that patients with fewer positive LNs had significantly more favorable DFS and OS [2021]. Recently, Solak et al [22] reported a clearer prognostic separation for TNBC using NR as compared to using pN staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that positive cathepsin D results may help to determine the patients with risk and to select more or less aggressive adjuvant therapy for the patients with early stage breast cancer during first 3-year follow-up (18). Huang et al (19) showed triplenegative breast carcinoma were frequently associated with overexpression of cathepsin-D, and with aggressive disease course through lymph node invasion and high cancer cell proliferation/Ki-67 index. Guerra et al (20) reported high level of p53 and cathepsin D, together with down-regulation of Bcl-2 is correlated with aggressiveness in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of our results, we can speculate that this effect may be more apparent in TNBC. On the other hand, there are some studies presenting contrary results in which lower proliferation rate was associated with better prognosis in patients with TNBC [30,[40][41][42] or in which no relation between Ki-67 LI and survival of women with TNBC was seen [43]. We think that these discrepancies, as suggested by International Ki-67 in Breast Cancer Working Group [26], can be caused by differences between analyzed patient groups according to clinical characteristics and treatment type.…”
Section: Discussionmentioning
confidence: 95%